Synclinic and anticlinic properties of (R, S) 4′-(1-methylheptyloxycarbonyl)biphenyl-4-yl 4-[7-(2, 2, 3, 3, 4, 4, 4-heptafluorobutoxy)heptyl-1-oxy]benzoates. (3rd July 2019) - Urbańska, M.; Dziaduszek, J.; Strzeżysz, O.; Szala, M.
ABSTRACT: Four racemic mixtures were synthesized and characterized. Their mesomorphic properties, such as phase transitions temperatures and enthalpies, were measured by a polarizing optical microscope and differential scanning calorimetry. The influence of one racemic mixture on the properties of the OAFLC mixture W-1000 was studied. The results show a wide temperature range of the SmCA * phase in this new mixture. The helical pitch was measured by spectrophotometry method. The electro-optical properties of the mixture were also presented and discussed.